Harp - Dunne, John Gregory 1932-2003 (Simon and Schuster, 1989)
The author's reflection on his life and what it means to be Irish in America.
Keywords: Dunne, John Gregory; Dunne, John Gregory <1932-2003>; Geschichte 1900-2000; English literature; United States; Authors, American -- 20th century -- Biography; USA; Biografie